Complete androgen insensitivity syndrome coexisting with müllerian duct remnants: a case report and literature review - Chen, De-lu; Guo, Song; Chen, Qiu-li; Qiu, Shan-jiao; Xu, Yu-ying; Zhang, Jun; Ma, Hua-mei; Li, Yan-hong (Frontiers in Pediatrics, 2024)
This study represents the first documentation of the coexistence of complete androgen insensitivity syndrome (CAIS) with Müllerian duct remnants (MDRs) in mainland China. Additionally, we provide a comprehensive review of the existing literature concerning CAIS with MDRs resulting from androgen receptor (AR) gene mutations. This study broadens the clinical spectrum of CAIS and offer novel insights for further exploration into Müllerian duct regression. A 14-year-old patient, initially raised as female, presented to the clinic with complaints of "primary amenorrhea." Physical examination revealed the following: armpit hair (Tanner stage 2), breast development (Tanner stage 4 with bilateral breast nodule diameter of 7 cm), sparse pubic hair (Tanner stage 3), clitoris measuring 0.8 cm × 0.4 cm, separate urethral and vaginal openings, and absence of palpable masses in the bilateral groin or labia majora.The external genital virilization score was 0 points. Serum follicle-stimulating hormone level was 13.43 IU/L, serum luteinizing hormone level was 31.24 IU/L, and serum testosterone level was 14.95 nmol/L. Pelvic magnetic resonance imaging (MRI) did not reveal a uterus or bilateral fallopian tubes, but nodules on both sides of the pelvic wall indicated cryptorchidism. The karyotype was 46,XY. Genetic testing identified a